THREATS TO THE FINANCIAL SECURITY OF UKRAINIAN BANKING INSTITUTIONS UNDER THE CONDITIONS OF DIGITALIZATION (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. The relevance of the study is due to the need to investigate threats to the financial security of the banking sector of Ukraine in the context of global digitalization of the financial space. The banking system of Ukraine is currently facing a dual problem, in particular, the pace of innovation and investment activities of banks and global technological progress contribute to the emergence of new banking innovations, while on the other hand, the Ukrainian banking system faces numerous internal risks and threats. The ability to minimize the negative impact of such threats, timely detection and neutralization of them contributes to the improvement of the financial security of banking institutions, taking into account the level of their innovation and investment activities.The purpose of the article. The aim of the paper is to study threats to the financial security of banking institutions in the context of digitalization of the financial space and active use of banking innovations by commercial banks.Metods. In order to achieve this goal, the authors used the following research methods: analysis and synthesis, systematization, abstract thinking, and scientific abstraction.Results.  In the article, the authors systematize scientific approaches to defining the essence of financial security of a banking institution and propose the author's approach to its typological characteristics with due regard for digitalization. The study also classifies threats to the financial security of banking institutions.Conclusiоns. It is substantiated that all threats to the financial security of banking institutions are divided into internal and external. Based on a critical analysis, the author's own approach to systematizing external and internal threats to the financial security of banking institutions in the context of intensifying their innovation activities is proposed, in particular, threats to the financial security of commercial banks are allocated by such features as: general economic situation; financial condition and financial stability; technological and digitalization; competitive environment; level of management and human resources; martial law.
Keywords: banking sector, banking system, financial security, banking institutions, banking innovations, investments, innovations, threats, digitization (digitalization)